MULTIFACTORIAL ANALYSIS OF THE FEATURES OF THE COURSE OF ATOPIC DERMATITIS IN CHILDREN IN THE ULYANOVSK REGION - Соколова, Татьяна Вениаминовна; Кафарова, Александра Игоревна; Соловьева, Ирина Леонидовна; Панченко, Лариса Андреевна; Смирнова, Виктория Алексеевна (Mother and Baby in Kuzbass, 2023)
According to the classification of atopic dermatitis (AD), there are 4 age periods of the disease. The existing Clinical Guidelines for AD (2021) contain clinical criterias of the disease in the absence of their quantitative assessment for various age periods. Multifactorial analysis of causally significant indicators is the basis for improving therapy.The aim of the research is to quantify the occurrence of clinical and laboratory markers of AD in children in the Ulyanovsk region, taking into account the age periods of the disease.Materials and methods. A retrospective analysis of medical documentation data was carried out in 326 children with AD (2019-2022). The author's version of the individual registration card was used. There were 149 infants, 151 children, and 26 adolescents. Statistical processing of the material was carried out using the Pearson criterion (χ2) and Spearman correlation analysis.Results. Quantitative characteristics of clinical manifestations of AD in children, taking into account age periods, indicate the predominance of a more severe course in adolescents: the maximum value of the SCORAD scale (39,78 ± 5,71 points); a high rate of recurrent course (84,6 %); the presence of lichenification (80,8 %) with its sharp severity (42,3 %); diffuse process (34,6 %); prevalence of complications (73,1 %), including those caused by combined bacterial and mycotic infection (30,8 %); the maximum registration of bronchial asthma (19,2 %), allergic conjunctivitis (23,1 %), concomitant pathology of various genesis (73,1 %) and IgE-mediated process (100 % of cases) by determining the general and specific IgE.Conclusion. Multifactorial analysis of the frequency of registration of clinical characteristics of AD and the results of laboratory examination of patients allowed us to quantify the features of the course of the disease, taking into account its age periods.